Aquatic insect assemblages in four urban lakes of Bogor, West Java, Indonesia - Wakhid Wakhid; Aunu Rauf; Majariana Krisanti; I Made Sumertajaya; Nina Maryana (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wakhid, Rauf A, Krisanti M, Sumertajaya IM, Maryana N. 2020. Aquatic insect assemblages in four urban lakes of Bogor, West Java, Indonesia. Biodiversitas 21: 3047-3056. Urban lakes represent important habitats for some freshwater organisms and support a high diversity of insect fauna. Study was conducted with the objectives to determine and compare aquatic insect assemblages in four urban lakes of Bogor, West Java, Indonesia. Insects were collected in the littoral zone using D-net at a certain interval along the perimeter of each lake. Sampling was carried out monthly during March, April, and May 2017. A total of 6,686 individuals representing 82 species/morphospecies, 28 families, and seven orders were recorded. Estimation of species richness by Chao1 suggested that sampling completeness for Situ Babakan, Situ Burung, Situ Gede, and Situ Tonjong were 88.71%, 75.86%, 82.17%, and 95.23%, respectively. Rarefaction curves indicated that more sampling would record a higher species richness. The least species richness and diversity of aquatic insect assemblages occurred in Situ Babakan characterized by high organic pollution due to fish farming. Canonical correspondence analysis showed that certain environmental factors were related to some species. Chironomus sp. (Diptera: Chironomidae), Micronecta ludibunda (Hemiptera: Micronectidae), and Anisops bouvieri (Hemiptera: Notonectidae) were associated with organically polluted water. Odonates such as Pseudagrion sp.1 (Coenagrionidae), Rhinocypha sp. (Chlorocyphidae), Acisoma panorpoides, Orthetrum sabina (Libellulidae), and Crocothemis servilia (Libellulidae) were associated with conditions of a high density of macrophytes. Our study provides baseline data for future monitoring and conservation management of these lakes.